2011
DOI: 10.1016/j.ajpath.2011.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Apelin Attenuates UVB-Induced Edema and Inflammation by Promoting Vessel Function

Abstract: Apelin, the ligand of the G protein-coupled receptor APJ, is involved in the regulation of cardiovascular functions, fluid homeostasis, and vessel formation. Recent reports indicate that apelin secreted from endothelial cells mediates APJ regulation of blood vessel caliber size; however, the function of apelin in lymphatic vessels is unclear. Here we report that APJ was expressed by human lymphatic endothelial cells and that apelin induced migration and cord formation of lymphatic endothelial cells dose-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 34 publications
4
34
0
Order By: Relevance
“…In addition, this alteration of lymphatic vasculature in apelin-KO mice was accompanied by a polarization of macrophages towards the M1 proinflammatory phenotype, suggesting a defect in the lymphatic barrier in protecting from edema and immune cell trafficking. These observations are in accordance with previous literature showing that apelin has an antiinflammatory action (39). Here, our data further indicate that the alteration of lymphatic vessels may account for the development of the proinflammatory condition.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In addition, this alteration of lymphatic vasculature in apelin-KO mice was accompanied by a polarization of macrophages towards the M1 proinflammatory phenotype, suggesting a defect in the lymphatic barrier in protecting from edema and immune cell trafficking. These observations are in accordance with previous literature showing that apelin has an antiinflammatory action (39). Here, our data further indicate that the alteration of lymphatic vessels may account for the development of the proinflammatory condition.…”
Section: Discussionsupporting
confidence: 94%
“…This observation is in line with the hypothesis that the activation of lymphatic vessels in early-phase MI may have a beneficial role in stimulating lymphangiogenic growth in the chronic phase of MI. Apelin has a pleiotropic action, facilitating cardiomyocyte contractility (19,42) and angiogenesis (21,43), but also limiting inflammation (39) and lowering blood pressure (18,44). Although the expression of APJ argues for a direct role of apelin in lymphatic endothelium, all of these effects of apelin on the cardiac microenvironment may indirectly influence the lymphatic function.…”
Section: Discussionmentioning
confidence: 99%
“…Apelin, an endogenous ligand orphan G protein–coupled receptor (APJ), is expressed widely in the vascular endothelium and promotes stabilization of lymphatic vessels in inflamed tissues (Sawane et al, 2011). Initially, it was described that apelin attenuates edema formation and UVB-induced inflammation by promoting lymphatic function in vivo (Sawane et al, 2011).…”
Section: A Bi-directional Cross-talk Between the Lymphatic Vasculaturmentioning
confidence: 99%
“…Initially, it was described that apelin attenuates edema formation and UVB-induced inflammation by promoting lymphatic function in vivo (Sawane et al, 2011). Additional studies proposed a new anti-obesity strategy based on enhancement of lymphatic and blood vessel integrity mediated by apelin treatment (Sawane et al, 2013).…”
Section: A Bi-directional Cross-talk Between the Lymphatic Vasculaturmentioning
confidence: 99%
“…Recently several new mediators of lymphangiogenesis have been identified that act through a direct mechanism or through VEGF family members (Cao et al, 2006;Kang et al, 2009;LarrieuLahargue et al, 2010;Sawane et al, 2011). Although VEGF-C and VEGF-D represent the principal mediators of lymphangiogenic process during development and under pathological condition, VEGF-A has been also demonstrated to stimulate this process due to its capacity to bind VEGFR-3 expressed on LEC (Koch et al, 2011).…”
Section: Discussionmentioning
confidence: 97%